Investigations into the larval rearing of two South African sparid species - Davis, Jerome Adam (Rhodes University, Faculty of Science, Department of Ichthyology and Fisheries Science, 1997)
The most significant bottleneck to the development of marine finfish culture is a reliable production of juveniles for growout. This is due to the small size at hatch and delicate nature of the pelagic larvae produced by most commercially desirable species. However, over the last 30 years, improved larviculture techniques have been developed to the extent that many species are being successfully cultured worldwide. These techniques were applied to two endemic species as a preliminary step towards establishing marine finfish aquaculture in South Africa. Adult roman Chtysoblephus laticeps and carpenter Argyrozona argyrozona (Pisces: Sparidae) were caught in the Tsitsikamma National Park. Both species responded to injection with pituitary extract, HCG and LHRHa, and were succesfully stripped up to 48 hours after injection. Fish were stripped twice, the second stripping producing better quality eggs. Chyrysoblephus laticeps also spawned naturally after injection with LHRHa. The fertilised eggs were incubated and the larvae reared in a fully recirculating seawater system. One batch of A. argyrozona and three batches of C. laticeps were reared through metamorphosis on a diet of enriched rotifers and Anemia, and inert foods, following commonly used rearing procedures. Both species followed developmental patterns of other cultured larvae, displaying typical critical stages; high mortalities at first-feeding and cannibalism from 26-30 days after hatch resulted in survival rates ranging from 0.1-0.5%. Growth, survival, size of gape at first-feeding, and ease of weaning onto an inert diet of C. laticeps was comparable to other species being reared for the first time, indicating some potential as a candidate species. The numbers of A. argyrozona larvae reared were insufficient to make comparisons with other studies. The adults also proved to be susceptible to physical damage while in captivity and were, therefore, considered unsuitable for aquaculture. The thesis describes the spawning procedure, the systems developed and the larval rearing process. The critical stages of first-feeding, swim bladder inflation, settlement and cannibalism are discussed and the development of the larvae described. The ontogeny of both species is described in detail. Both species displayed typical sparid developmental patterns, but differed with respect to pigmentation, head spination and morphometrics.
Keywords: Sparidae